An investigation into the application of the IEEE 1394 high performance serial bus to sound installation contro - Klinkradt, Bradley Hugh (Rhodes University, Faculty of Science, Department of Computer Science, 2003)
This thesis investigates the feasibility of using existing IP-based control and monitoring protocols within professional audio installations utilising IEEE 1394 technology. Current control and monitoring technologies are examined, and the characteristics common to all are extracted and compiled into an object model. This model forms the foundation for a set of evaluation criteria against which current and future control and monitoring protocols may be measured. Protocols considered include AV/C, MIDI, QSC-24, and those utilised within the UPnP architecture. As QSC-24 and the UPnP architecture are IP-based, the facilities required to transport IP datagrams over the IEEE 1394 bus are investigated and implemented. Example QSC-24 and UPnP architecture implementations are described, which permit the control and monitoring of audio devices over the IEEE 1394 network using these IP-based technologies. The way forward for the control and monitoring of professional audio devices within installations is considered, and recommendations are provided.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Digital electronics; Sound -- Recording and reproducing -- Digital techniques; Music -- Data processing; Computer sound processing